A review of findings on agent spawning and mobility - Alshaki O.T.; Ahmad M.S.; Mahmoud M.A. (Asian Research Publishing Network, 2023)
Mobile agent technology is becoming more popular and has been implemented in many areas. Several research have been conducted to address its challenges including two of the most important which are agent spawning and agent mobility. This paper reviews the mobile agent technology, the background concept of mobile agent cloning and spawning, agent mobility as well as the problems faced by many researchers during their research on mobile agent. Various mobile agent types are also discussed. The paper finally proposes a new agent spawning and mobility models to resolve some of the researchers problems. 2005 ongoing JATIT & LLS.